A portfolio selection of internet of things (IoTs) applications for the sustainable urban transportation: A novel hybrid multi criteria decision making approach - Heidary Dahooie, Jalil; Mohammadian, Ayoub; Qorbani, Ali Reza; Daim, Tugrul (Technology in society, 2023)
The nature of technological innovations is unpredictable, therefore decision making on disruptive technologies such as the Internet of Things (IoT) in many public sector organizations is undisciplined. Due to resource limitations and tremendous payoffs, there is a need to have a decision-making framework to manage technological innovations as a portfolio of investments that balances risk and reward simultaneously. This study provides a new portfolio matrix for decision making to identify IoT applications in the urban transportation sector for future investment based on two dimensions of impact on sustainable development (SD) and feasibility for implementing IoT using a novel hybrid multi criteria decision making approach. For this purpose, seventeen IoT applications in urban transportation were identified using a systematic literature review. The improved Fuzzy Cognitive Map (FCM) - Best Worth Method (BWM) method was used to determine the relationship between SD criteria and IoT challenges, and to calculate their importance. Then, the Additive Ratio Assessment (ARAS) method was used to prioritize the IoT applications based on SD criteria and IoT challenges. Finally, the adapted impact-feasibility matrix was used to simultaneously evaluate both criteria for selecting the IoT applications portfolio. Results of this paper show that bike sharing and car sharing have the first priority for investment in the case of a developing country. •Internet of Things (IoT) in Transportation•A decision-making framework to manage technological innovations.•A portfolio of investments that balances risk and reward simultaneously•Feasibility for implementing IoT using a novel hybrid FCM-BWM-ARAS